Dupilumab combined with low‐dose systemic steroid therapy improves efficacy and safety for bullous pemphigoid. Issue 8 (1st July 2022) - Yang, Jin; Gao, Haiqing; Zhang, Zhen; Tang, Chang; Chen, Zihua; Wang, Lanting; Yang, Fanping; Chen, Shengan; He, Shan; Liu, Shutao; Tang, Lin; Xu, Yu; et al.
Abstract: Routine systemic therapy for bullous pemphigoid (BP) has been challenged due to the inevitably adverse effects. According to the successful applications of dupilumab in BP cases reported, therefore, we investigate the real‐life efficacy and safety of dupilumab combined with low‐dose oral steroid for BP. A cohort of BP patients who received either dupilumab plus low‐dose methylprednisolone (dupilumab group) or merely methylprednisolone (control group) was retrospectively reviewed. The time to disease control was investigated. Additionally, the control dose and cumulative dosage of steroids, Bullous Pemphigoid Disease Area Index (BPDAI) scores, pruritus scores, and adverse events were assessed. A total of 40 patients, with 20 in each group, were retrospectively studied. The time to disease control was shorter in the dupilumab group than the control group (14 days vs. 19 days, p  = 0.043). When the disease was controlled, the control dose and cumulative dosage of methylprednisolone in the dupilumab group were substantially lower than those of the control (24.6 mg vs. 48.8 mg, 376.8 mg vs. 985.6 mg, both p  < 0.01). Compared with the control, the percentage change from baseline in BPDAI scores and pruritus scores were both significantly reduced, and the adverse events were also less frequent in the dupilumab group. The combination therapy of dupilumab plus low‐dose methylprednisolone exhibits superior efficacy and safety in comparison with the current first‐line systemic therapy for BP.